Environmental regulations in eco-innovation and sustainable performance in Mexican Automotive Industry - Gonzalo Maldonado-Guzmán; Víctor Manuel Molina-Morejón; Raymundo Juárez del Toro (La Granja: Revista de Ciencias de la Vida, 2024)
In the literature, evidence has been provided that establishes that compliance with environmental regulations promotes the adoption and implementation of eco-innovation activities in manufacturing firms, since through this type of activities not only are the costs associated with the discharges of pollutants, but also increases the level of sustainable performance of companies. However, little is known about the relationship between environmental regulations, eco-innovation, and sustainable performance, since there are few studies published in the literature that have focused on their analysis, so this study aims to fill this existing gap, and generate new knowledge of the relationship between these three constructs through an extensive review of the literature. Likewise, a questionnaire was distributed to a sample of 460 manufacturing firms in Mexico, analyzing the data through confirmatory factor analysis and structural equation models based on covariance. The results obtained suggest that environmental regulations have positive effects on eco-innovation, and eco-innovation has positive effects on sustainable performance of manufacturing firms in the automotive industry. In this context, the results obtained allowed us to conclude that compliance with environmental regulations established by the public administration, by manufacturing firms in the automotive industry, improve both eco-innovation activities and sustainable performance of organizations.